Pengaruh Pengetahuan Keuangan, Perilaku Keuangan, dan Gaya Hidup terhadap Kesejahteraan Keuangan pada Generasi Z - Habibah, Ni'matul; Saputra, Irwan Adimas Ganda (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This study aims to determine the influence of financial knowledge, financial behavior, and lifestyle on financial well-being in Generation Z. This study uses a descriptive quantitative approach with the purposive sampling method. Data processing was carried out with SPSS version 25, while the data technique used data analysis using multiple linear regression. The results show that financial knowledge does not have a significant influence on financial well-being, while financial behavior and lifestyle have a significant influence on financial well-being.